Dialectology of Surigaonon in San Francisco, Surigao Del Norte: Preliminary Linguistic Study - BONOTAN, RINALYN (International Journal of Language and Literary Studies, 2025)
This study investigates the dialectal variation of the language spoken in San Francisco, Surigao del Norte. The research was motivated by local observations that certain words differ across adjacent barangays. Using the principles of dialectology, the study aims to provide empirical support for these perceived linguistic variations. To analyze the differences, the researcher used 150 Swadesh words to compare lexical items across six barangays. The results reveal that, even at the lexical level, variations are evident among these barangays. High lexical similarity was observed between Diaz and Poblacion, both primarily Surigaonon-speaking. However, as barangays are located farther from Surigao City—the capital of Surigao del Norte and neighboring the town of San Francisco—the presence of cognates from other languages increases. Specifically, the study found that cognates are distributed as 54% Cebuano, 32% Surigaonon, 12% Boholano, and 2% Minamanwa. This preliminary study highlights the complex linguistic landscape of San Francisco, Surigao del Norte, showing how geographic distance and community interaction influence dialectal variation. It also contributes to the broader understanding of the relationships between Surigaonon and surrounding native languages, offering a foundation for future, more detailed dialectological research.